2019
DOI: 10.1016/j.waojou.2019.100035
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in relation to asthma and allergy modified by abdominal obesity: The HUNT study in Norway

Abstract: Objective It is unknown whether the decreasing prevalence of H. pylori infections is associated with the increase in obesity and asthma and allergy. In this study, we assessed if obesity plays an intermediate role between H . pylori infections and allergy. Design A population-based, nested case-control study of 10,005 participants within the second Nord-Trøndelag Health Study (HUNT2), Norwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…This suggests that H. pylori infection can lead to a Th1-polarized immune response, as IL-4 is a cytokine that induces characteristic Th2 responses ( Bamford et al, 1998 ; Sommer et al, 1998 ). On this basis, through suppression of the Th2 response, H. pylori infection might also decrease the risk of asthma and allergies ( Ness-Jensen et al, 2019 ). Therefore, those in support of the hygiene hypothesis believe that it will not only be the relatively bacteria-free environment in early life, but also the use of antibiotics that increases the risk of autoimmune disorders in later life ( Miftahussurur et al, 2017 ).…”
Section: Pros and Cons Of Helicobacter Pylori Treamentioning
confidence: 99%
“…This suggests that H. pylori infection can lead to a Th1-polarized immune response, as IL-4 is a cytokine that induces characteristic Th2 responses ( Bamford et al, 1998 ; Sommer et al, 1998 ). On this basis, through suppression of the Th2 response, H. pylori infection might also decrease the risk of asthma and allergies ( Ness-Jensen et al, 2019 ). Therefore, those in support of the hygiene hypothesis believe that it will not only be the relatively bacteria-free environment in early life, but also the use of antibiotics that increases the risk of autoimmune disorders in later life ( Miftahussurur et al, 2017 ).…”
Section: Pros and Cons Of Helicobacter Pylori Treamentioning
confidence: 99%
“…By affecting immune and inflammatory responses [ 78 , 92 , 431 , 432 , 433 ]. HPI may protect against asthma and allergy (particularly in children), autoimmune disorders (systemic lupus erythematosus, rheumatoid arthritis [RA] and multiple sclerosis, coeliac disease), inflammatory bowel disease (especially Crohn’s disease), eosinophilic esophagitis, eczema, obesity [ 9 , 78 , 342 , 433 , 434 , 435 , 436 , 437 , 438 , 439 , 440 , 441 ] and tooth loss [ 442 ]. Negative associations between these diseases and HPI (beneficial effects) were observed mainly in patients colonized with cagA+ strains of H.p.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…In a case-control study, including more than 10 000 patients, H pylori infection was found in 31%, asthma in 10.4%, and allergic rhinitis in 16% of the patients, but without any significant association; however, in patients with abdominal obesity, H pylori infection was associated with a 30%-40% reduced OR of asthma and a 25% reduced OR of allergic disorders. 91 Moreover, in a case-control study of 27 paediatric patients with asthma and 54 controls, an inverse association between H pylori and asthma was found (OR 0.1, 95% CI, 0.039-0.305; P = .026). 92 In a cohort study, 16% of children who were uninfected at 2 and 10 years of age developed asthma at 16 years vs none of those with H pylori infection at 2 years of age.…”
Section: Allergic Disordersmentioning
confidence: 98%